Palavras e Imagens na educação de pessoas jovens e adultas: onde está o sujeito? - De Camargo, Maria Rosa Rodrigues Martins [UNESP] (My University, 2014)
It is built upon queries with regard to the act of writing as a direct relation to the object, the writing process, and the subject-writer-author. Such proposition addresses some issues with respect to the place attributed to the subject in educational research: where can the subject be found in the order of the political, educational and investigative discourse? Accordingly, these questions were answered as reported by the participants of the study. The results obtained open space to unprecedented ways to relate to subjects and objects, contributing to the field of studies in the education of young people and adults.
Words and Images in the education of young people and adults: Where is the subject?
Keywords: Act of writing; Subject of writing; Young and adults education